Analisis Controlling System Pada Teknologi Pengendalian Kualitas Kopi - Tanjung, Ade Firmansyah; Kembaren, Emmia Tambarta; Sinta, Irada; Fadli, Fadli (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2024)
It is important to maintain the quality of coffee beans in accordance with market desires, therefore it is necessary to carry out the quality control process stages through Six Sigma method analysis to identify the causes of problems with damage or defects in coffee beans. This research was conducted at the Cooperative KBQ Baburrayyan which is located in Central Aceh Regency, Aceh Province. The data analysis method used in the research was the six sigma method and fishbone diagram analysis. The research results obtained were from the process of defining problems with the quality of Arabica coffee beans, there were 3 causes of the highest defective coffee beans occurring, namely during the purchasing, drying and sorting processes.